Biogeographical implications of Zambezian Cichlidogyrus species (Platyhelminthes: Monogenea: Ancyrocephalidae) parasitizing Congolian cichlids - Vanhove, Maarten P.m.; van Steenberge, Maarten; Dessein, Steven; Volckaert, Filip A.m.; Snoeks, Jos; Huyse, Tine; Pariselle, Antoine (Zootaxa, 2013)
Fishes normally restricted to inland waters are valuable model systems for historical biogeography, inter alia, because of their limited dispersal abilities and concordance with the distribution patterns of other freshwater taxa (Zogaris et al. 2009). The comparison of fish species assemblages has been the major biogeographical tool for delineating African aquatic ecoregions as the fossil record is often meagre and merely offers complementary information. This is, for example, the case for the Zambezian and Congolian ichthyofaunal provinces, which display substantial contemporary fish diversity (Stewart 2001). Between both regions lies the Bangweulu-Mweru ecoregion (sensu Scott 2005), known for its high percentage of endemicity. Although hydrographically belonging to the Congo Basin, the Bangweulu-Mweru ecoregion has a high affinity with the Zambezi province (Scott 2005), due to historical river connections (Tweddle 2010). Studies comparing the Zambezi and Congo ichthyofaunal provinces are rare and hampered by lack of data from the Congo Basin. The latter harbours more than 1250 fish species (Snoeks et al. 2011) while in the Zambezi, only 120 freshwater fishes are found (Tweddle 2010). Indeed, species richness declines in all major African teleost families from the Congo Basin southwards, riverine haplochromine cichlids forming a notable exception to this rule (Joyce et al. 2005). Although it was hypothesized by Tweddle (2010) that the origin of many Zambezian fish species is in the Congo Basin, the haplochromines Serranochromis Regan, Sargochromis Regan, Pharyngochromis Greenwood and Chetia Trewavas, together forming the serranochromines, have their centre of diversity in the rivers of the Zambezian ichthyofaunal province (Joyce et al. 2005). Therefore, the biogeographical history of Cichlidae across the Zambezi- Congo watershed is not only key to cichlid biogeography on an African scale, but also complementary to biogeography of all other teleosts in the region. Yet, colonisation and speciation patterns are difficult to unravel due to complex hydrological history (Katongo et al. 2007; Schwarzer et al. 2012).